Photobiomodulation and Antimicrobial Photodynamic Therapy for Oral Ulcers in a Patient With Thrombocytopenia Following Bone Marrow Transplantation: Phototherapies for Oral Ulcers - Campos, Luana; Campanhã, Daniel; Yudi Tateno, Ricardo; Felipe Palma, Luiz (Journal of Lasers in Medical Sciences, 2022)
Introduction: Thrombocytopenia is usually seen after allogeneic hematopoietic stem cell transplantation (HSCT) and may favor the development of oral bleeding, infections, and ulcerations. Case Report: A patient with chronic myelomonocytic leukemia had been submitted to allogeneic HSCT. Within a few days, she developed severe thrombocytopenia and an extensive ulcerative area comprising both lips, which bled spontaneously, as well as smaller ulcers on the tongue mucosa. The lesions were managed using a combination of phototherapies (photobiomodulation and antimicrobial photodynamic therapies), totalizing 4 laser sessions. After 4 days, there was an important reduction in the severity of the lesions, with spontaneous disappearance of the crusts and reepithelization. Conclusion: The proposed combination of phototherapies would be a suitable therapeutic modality for the management of oral lesions related to platelet disorders induced by oncologic treatments. Doi:10.34172/jlms.2022.17.